Key features of hip hop dance motions affect evaluation by judges - Sato, N.; Nunome, H.; Ikegami, Y. (Journal of Applied Biomechanics, 2014)
The evaluation of hip hop dancers presently lacks clearly defined criteria and is often dependent on the subjective impressions of judges. Our study objective was to extract hidden motion characteristics that could potentially distinguish the skill levels of hip hop dancers and to examine the relationship between performance kinematics and judging scores. Eleven expert, six nonexpert, and nine novice dancers participated in the study, where each performed the "wave" motion as an experimental task. The movements of their upper extremities were captured by a motion capture system, and several kinematic parameters including the propagation velocity of the wave were calculated. Twelve judges evaluated the performances of the dancers, and we compared the kinematic parameters of the three groups and examined the relationship between the judging scores and the kinematic parameters. We found the coefficient of variation of the propagation velocity to be significantly different among the groups (P < .01) and highly correlated with the judging scores (r = -0.800, P < .01). This revealed that the variation of propagation velocity was the most dominant variable representing the skill level of the dancers and that the smooth propagation of the wave was most closely related to the evaluation by judges.